Overcoming talent shortage through impact sourcing - Aini Aman; Yusasniza Mohd Yunus; Zaini Embong; Ruhanita Maelah; Abdul Aziz Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to understand the use of impact sourcing strategy to overcome talent shortage issues in global business services (GBS) firms located in Malaysia and Sri Lanka. These countries were selected because of their potential development in impact sourcing. This study uses qualitative research approach with two selected case studies of GBS firms with impact sourcing operations. The selected GBS firms involved in impact sourcing of their finance and accounting processes to marginalized communities in Malaysia and Sri Lanka. Findings show that the impact sourcing is used as a strategy to overcome talent shortage issues faced by GBS firms. At the same time, it contributes to income generation with world class work experiences among the marginalized communities. Practically, this opportunities are better gained with high firm’s readiness towards working closely with the marginalized communities in mitigating the talent shortage issues. Theoretically, this study provides empirical evidence of global talent management in the context of impact sourcing in GBS firms. It further contributes to the literatures in impact sourcing of accounting activities in Malaysia and Sri Lanka that reach out young talents from marginalized communities at the universities and those in the rural areas.